The Poetics of Traditional Ghanaian Beads (Global Journal of Human-Social Science, 2015)
The use of beads in Ghana is a site for a robust cultural meaning-making. Beads have been very popular in the past and are growing stronger in popularity with modernity to the extent that their modern meanings seem to be eclipsing the traditional ones. This paper takes us back to their traditional meanings by examining closely their relationship with the wearer. Using qualitative instruments of research methodology basically through interviews and participant observation, this paper, by examining the bead as a cultural text, identifies two main relationships between the bead and the wearer: the synecdochic and the metonymic relationships. Using mainly linguistic theories to interrogating these relationships, the paper, relying on the entextualization theory of Michael Silverstein and Greg Urban and the performance theory of Richard Bauman, discovers that in addition to being objects of aesthetics as the modern meanings mainly suggest, the bead has very important traditional meanings. The paper also demonstrates that where the bead is placed on the body is a function of traditional meanings. Again, when the bead is used is also contingent upon traditional meanings.
Keywords: entextualization; performance; aesthetics; metaphor; beads